Long-Lived Antibody and B Cell Memory Responses to the Human Malaria Parasites, Plasmodium falciparum and Plasmodium vivax - Wipasa, Jiraprapa (Public Library of Science, 2010)

(untitled)
Antibodies constitute a critical component of the naturally acquired immunity that develops following frequent exposure to malaria. However, specific antibody titres have been reported to decline rapidly in the absence of reinfection, supporting the widely perceived notion that malaria infections fail to induce durable immunological memory responses. Currently, direct evidence for the presence or absence of immune memory to malaria is limited. In this study, we analysed the longevity of both antibody and B cell memory responses to malaria antigens among individuals who were living in an area of extremely low malaria transmission in northern Thailand, and who were known either to be malaria naïve or to have had a documented clinical attack of P. falciparum and/or P. vivax in the past 6 years. We found that exposure to malaria results in the generation of relatively avid antigen-specific antibodies and the establishment of populations of antigen-specific memory B cells in a significant proportion of malaria-exposed individuals. Both antibody and memory B cell responses to malaria antigens were stably maintained over time in the absence of reinfection. In a number of cases where antigen-specific antibodies were not detected in plasma, stable frequencies of antigen-specific memory B cells were nonetheless observed, suggesting that circulating memory B cells may be maintained independently of long-lived plasma cells. We conclude that infrequent malaria infections are capable of inducing long-lived antibody and memory B cell responses.